Ecological Responsibility as a Component of Professional Preparedness Formation of Technology Teacher - LivshunОleksander (Pedagogical Discourse, 2012)
The article studies the meaning of ecological responsibility as one of main features of forming professional preparedness of technology teacher. The notion of professional preparedness and professional aptitude has been defined. The necessity and importance of ecology as a science for the whole society has been analyzed as well.